2016
DOI: 10.3201/eid2212.160611
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Reassortant Avian Influenza A(H5N1) Virus Clade 2.3.2.1a in Poultry, Bhutan

Abstract: Highly pathogenic avian influenza A(H5N1), clade 2.3.2.1a, with an H9-like polymerase basic protein 1 gene, isolated in Bhutan in 2012, replicated faster in vitro than its H5N1 parental genotype and was transmitted more efficiently in a chicken model. These properties likely help limit/eradicate outbreaks, combined with strict control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…Currently, the global concern about H9N2 viruses is associated with their ability to donate their genes to other AIV giving rise to high and low pathogenic IAVs that could cross species barriers and infect humans ( Figure 6 ). In addition to the zoonotic H5N6, H7N9 and H10N8 AIV, the H9N2 viruses also donated their internal genes to other IAVs, such as avian H5N1 [ 140 , 141 ], H5N2 [ 136 , 141 ], H1N2, H3N2, H6N2 [ 141 ], and H6N6 [ 142 ].…”
Section: Evolution and Epidemiology Of Iavmentioning
confidence: 99%
“…Currently, the global concern about H9N2 viruses is associated with their ability to donate their genes to other AIV giving rise to high and low pathogenic IAVs that could cross species barriers and infect humans ( Figure 6 ). In addition to the zoonotic H5N6, H7N9 and H10N8 AIV, the H9N2 viruses also donated their internal genes to other IAVs, such as avian H5N1 [ 140 , 141 ], H5N2 [ 136 , 141 ], H1N2, H3N2, H6N2 [ 141 ], and H6N6 [ 142 ].…”
Section: Evolution and Epidemiology Of Iavmentioning
confidence: 99%
“…Influenza A virus (IAV) is highly infectious, and causes significant morbidity and mortality worldwide ( Ly et al, 2016 ; Marinova-Petkova et al, 2016 ; Thomas et al, 2017 ). Highly pathogenic avian influenza virus (H5N1-HPAIV) has been categorized as a List A disease by the International Office of Epizootics (OIE).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly detected clade in this region was 2.2. Clade 2.3.2.1a was also common and was identified in India, Bangladesh, Nepal and Bhutan [18][19][20] [18,24]. The co-detection of genetically related avian influenza viruses in human and poultry during the same period suggested that viruses were transmitted from poultry to human in Bangladesh Pakistan and Nepal.…”
Section: Discussionmentioning
confidence: 92%
“…H5N1 viral clades reported in poultry in South Asian countries, January 2003 to December 2018[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
mentioning
confidence: 99%